Detection and quantitative evaluation of pumping distress on bridge deck pavement through field and laboratory experiments. (16th May 2023) - Ren, Dongya; Shang, Jing; Xu, Jie; Huang, Mingxing; Chen, Xu; Cao, Chaofei; Ai, Changfa
Highlights: The paper quantitatively summarizes the distribution and development of pumping distress using various field and laboratory methods. The paper adopts GPR techniques to assess the structure of asphalt pavements. The paper identifies potential causes of the pumping phenomenon. The paper quantifies the extent and severity of the pumping distress. Abstract: Pumping distress refers to the phenomenon of dynamic water entering a pavement, soaking the cement concrete layer to form slurry, and being pumped out of the pavement void under the action of traffic loading. Pumping distress is frequently reported in high temperature and rainy regions, such as Sichuan province in China. Various factors contribute to pumping distress on bridge decks, but most of these factors have merely been subjected to qualitative assessment. The aim of the study is to conduct a comprehensive quantitative analysis through three years of field investigations and laboratory experiments. The field investigations include ground penetrating radar (GPR), pavement permeability tests, skid resistance tests, and drainage facilities surveys. The quantitative analysis of the field and laboratory inspections revealed that the formation reason, deterioration rate, and damage degree of pumping distress were different between the truck and emergency lanes. The occurrence of pumping distresses was significantly related to the uneven construction of the bridge deck leveling layer, compaction segregation, and poor drainage. Additionally, the influence of pavement thickness uniformity on pumping distress was evaluated by incorporating GPR techniques. Failure in the waterproof adhesion layer resulted in the barrier between the cement concrete deck and the asphalt mixture breaking, which allowed alkaline sources to move and transfer to the pavement layer easily. The outcomes of this study can help bridge authorities and construction contractors choose appropriate design and construction measures to prevent pumping distress.